The relationship between academic passions and critical thinking in a Chinese college student sample: a latent profile analysis - Wang, Shaojie; Fan, Xizhen; Yu, Hao; Yan, Xing; Wang, Jianmei; Liu, Ying; Li, Yue (Frontiers in Psychology, 2025)
BackgroundAcademic passions, including harmonious and obsessive passions, play a significant role in academic life by influencing students’ motivation, engagement, and overall academic success. Critical thinking is essential in education as it helps individuals assess, evaluate, and make informed decisions based on reasoning, which is crucial for academic growth and lifelong learning. Given the increasing emphasis on developing critical thinking skills in education, it is crucial to investigate how academic passions influence this cognitive process in the Chinese context.MethodsA total of 698 valid questionnaires were collected from college students from Guangdong and Hunan provinces in China. This study used latent profile analysis (LPA) to investigate the profiles of harmonious and obsessive passions. Then it tested differences in critical thinking based on the profiles of harmonious and obsessive passions.ResultsThree latent profiles for two academic passions were identified: low, medium, and high. Respondents in the high harmonious and obsessive passion profiles exhibited the significantly highest critical thinking abilities.ConclusionThe results confirm the heterogeneity of harmonious and obsessive passions. Students with higher levels of academic passions demonstrate enhanced critical thinking abilities compared to their peers. This study suggests that educators should pay attention to students’ academic passions when cultivating their critical thinking skills. This study offers several implications for practice. First, colleges should provide targeted counseling and guidance based on the types of students’ passion. Second, it is necessary to balance the relationship between harmonious and obsessive passions to promote students’ mental health and academic persistence. Third, colleges should help students develop harmonious passion, thereby improving their critical thinking ability.